HUBUNGAN TINGKAT PENGETAHUAN IBU PRIMIPARATENTANG ASI EKSKLUSIF DENGAN MOTIVASI PEMBERIANASI EKLUSIF PADA BAYI USIA 0 â 6 BULAN - Puji Suryantini, Naning; Ratnasari, Mila (JURNAL KEPERAWATAN SEHAT, 2015)
Breast feeding the baby was not only benefits but also can saved a family finance during the global crisis with increasing prices of infant formula. This study of this research was to analized the relationship of the level of knowledge of primipara mother breast milkexclusively with Exclusive breast feeding motivation in infants aged 0 – 6 months. The designe research was analytic crosssectional . The population was all mothers primipara who have infants ages 0-6 months in the Bakalan village Gondang subdistrict Mojokertoas many as 20 respondents, this research Sample using the technique of total sampling, the result of this research are the mothers knowledge of primipara largely on either a total of 16 categories of respondents (80%). The motivation mothers primipara in giving exclusive breast milk in infants ages 0-6 months most havepositive motivation as much as 19 respondents (95%). Based on the correlation of chi-square test revealed a significant value of p = 0.00, which means the value of p < 0.05.This shows there is a relationship between the mothers knowledge of primipara about breast milk exclusively with exclusive breast feeding motivation in Bakalan Village Gondang Subdistrict of Mojokerto. Midwife as health care personnel who are responsible for the safety of the mother and her baby must constantly provide information and encourage the motivation mothers to give breast milk exclusively.From the explanation above authors are interested in doing research on relationship ofthe level of knowledge of primipara mother breast milk exclusively with Exclusive breast feeding motivation in infants ages 0-6 monthsKeywords: Breast Milk Exclusively, Knowledge, Motivation, The Mother Of Primipara.